2023
DOI: 10.3389/fimmu.2023.1154552
|View full text |Cite
|
Sign up to set email alerts
|

The regulation of self-tolerance and the role of inflammasome molecules

Abstract: Inflammasome molecules make up a family of receptors that typically function to initiate a proinflammatory response upon infection by microbial pathogens. Dysregulation of inflammasome activity has been linked to unwanted chronic inflammation, which has also been implicated in certain autoimmune diseases such as multiple sclerosis, rheumatoid arthritis, type 1 diabetes, systemic lupus erythematosus, and related animal models. Classical inflammasome activation-dependent events have intrinsic and extrinsic effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 301 publications
0
3
0
Order By: Relevance
“…In recent years, food bioactive compounds, in particular fruit and vegetables rich in flavonoids and antioxidants, as NLRP3 inflammasome modulators, have been discussed as a whole, rather than a single nutrient or functional compound ( 227 ). However, there is a lack of human data on their activity on the NLRP3 activation and there is a widespread opinion that the inhibition of the inflammasome activation may only have a minimal effect, and would only contribute more significantly if an autoimmune response is already established ( 228 ).…”
Section: Avoidance Resistance and Tolerance To Virusesmentioning
confidence: 99%
“…In recent years, food bioactive compounds, in particular fruit and vegetables rich in flavonoids and antioxidants, as NLRP3 inflammasome modulators, have been discussed as a whole, rather than a single nutrient or functional compound ( 227 ). However, there is a lack of human data on their activity on the NLRP3 activation and there is a widespread opinion that the inhibition of the inflammasome activation may only have a minimal effect, and would only contribute more significantly if an autoimmune response is already established ( 228 ).…”
Section: Avoidance Resistance and Tolerance To Virusesmentioning
confidence: 99%
“…In chronic inflammation, a continuous immune response is often not properly regulated or controlled. 56,57 In this way, immune cells, such as macrophages, neutrophils, and lymphocytes, can continue to release inflammatory mediators such as cytokines, chemokines, and ROS, facilitating the prolongation of the inflammatory response. Numerous attempts have been made to identify the causes of the dysregulation of immune signaling pathways to prevent the development of chronic inflammation and chronic inflammatory diseases.…”
Section: Dysregulation Of Immune Signaling Pathwaysmentioning
confidence: 99%
“…Neuroinflammation has been identified to be a major factor in the neuropathology of MS, with inflammasome activation playing a critical role in the neuroinflammatory process [2][3][4][5][6]. Inflammasomes are protein complexes that can be activated by a wide range of stimuli [7].…”
Section: Introductionmentioning
confidence: 99%
“…Inflammasomes are protein complexes that can be activated by a wide range of stimuli [7]. The NOD-like receptor protein 3 (NLRP3) inflammasome is the most widely studied of the inflammasomes and has been shown to play a role in the neuropathology of MS [3][4][5][6][8][9][10][11][12][13]. Furthermore, in patients with MS, it has been shown that memory T cells exhibit a reduced ability to suppress NLRP3 inflammasome activation [14].…”
Section: Introductionmentioning
confidence: 99%